CURRÍCULO INTEGRADO NO PROEJA E A PERMANÊNCIA ESCOLAR: Na trilha de avanços e desafios - GOMES, Nathalia Rissane Costa (2022)
This study is part of the research group School, Curriculum, and Teacher Education. Formação Docente. It investigates the integrated curriculum of the National Program for the Integration of Vocational Integration of Professional and Basic Education in the modality of Youth and Adult Education and Adult Education - PROEJA in school permanence, with the main objective of to analyze the integrated curriculum of the technical course in computer network offered by PROEJA PROEJA in the Federal Institute of Education, Science and Technology - IFMA, São José de Ribamar campus José de Ribamar campus and its repercussions in the permanence of young people and adults in the course. course. In the fundamentation of this research, we searched for theorists who deal with the main categories of the study, as well as official documents such as laws, decrees, resolutions Resolutions, Institutional Development Plan (2019 - 2023), Institutional Institutional Pedagogical Project (2019-2023) and the course plan for the computer network of IFMA. Qualitative research was adopted as a methodological approach, conceiving the object of study in its historicity, movement and contradictions. It was used as a technique used as a technique for data collection the bibliographic research, the documentary research, and the field field research. The data collected were analyzed by means of content analysis content, where it was possible to use the expression analysis identifying the situation in the context of the course of the subjects involved, and the analysis of relationships from correlations between the elements. Thus, it was possible to identify that the organization of the integrated curriculum favors the strengthening of a comprehensive training. It was identified Some advances were also identified, such as a curricular proposal based on the integrated integrated curriculum, help from the institution to the students, a favorable relationship among peers, and the challenges that go through disciplines that are still juxtaposed, difficulty in the the relationship between theory and practice, teacher training, and the pandemic context itself, which also significantly influenced the permanence of students in the course, besides the challenges that have historically permeated the Youth and Adult Education modality. Adults. From the policy of PROEJA one can think of an advance, however, the challenges that have been revealed lead to the reflection that it is still necessary to put into effect policies and practices in the and practices in the school so that we can trace a real and significant advance of the integrated integrated curriculum and its repercussion on the permanence of young people and adults.